MORPHOLOGICAL CHARACTERISTICS, PRODUCTIVITY AND QUALITY OF THREE NAPIER GRASS (Pennisetum purpureum Schum) CULTIVARS HARVESTED AT DIFFERENT AGE - Budiman, B.; Soetrisno, R.D.; Budhi, S.P.S.; Indrianto, A. (Diponegoro University, 2012)
The research was conducted to determine the morphological characteristics, productivity andquality of Napier grass cultivars Taiwan, King and Mott harvested at 8 and 13 after planting. Effect ofcultivar and harvest arranged in a nested design (3x2). The variables were observed consisting ofmorphological characteristics, dry matter production and forage quality. The results showed that themorphological characteristics, leaf stem ratio, fiber content, crude protein content and in vitro dry matterdigestibility of Napier grass Taiwan and King cultivar were not different, but both morphologicalcharacteristics, fiber content was higher (P <0.05) compared to Mott cultivar, whereas leaf stem ratio,crude protein content and in vitro dry matter digestibility Mott cultivar was higher (P <0.05) comparedto Taiwan and King cultivars. In general, an increase in plant height and fiber content at the age of 13weeks, whereas crude protein content and in vitro dry matter digestibility decreased. It was concludedthat the highest dry matter production found in Taiwan and the King cultivars, whereas highest qualityfound in Mott cultivar. Dry matter production was highest harvested at 13 weeks, whereas the highestquality harvested at 8 weeks after planting for all cultivars tested.